Influence of H2S on the pitting corrosion of 316L stainless steel in oilfield brine. (15th April 2021) - Hesketh, J.; Dickinson, E.J.F.; Martin, M.L.; Hinds, G.; Turnbull, A.
Highlights: Impact of H2 S partial pressure on pitting of 316L SS in oilfield brines. Pitting most severe at intermediate partial pressures of H2 S. pH of pit solution controls solubility of metal sulphides and availability of free H2 S. Metal sulphide formation proposed to limit pit development at higher partial pressures. Abstract: Coupon immersion tests were performed on 316L stainless steel in a simulated oilfield environment to evaluate the effect of H2 S partial pressure on pit depth and density. Pitting was most significant at intermediate partial pressures of H2 S, for which free H2 S in the pit solution is maximised. Inhibition of pitting at higher partial pressures is attributed to blocking of the pit surface by metal sulphide phases. The key role of pH in the pit solution is to determine the solubility of metal sulphides and the availability of free H2 S to adsorb on the reacting pit surface and sustain activity.